Examining the Gender Wealth Gap in Germany - Eva M. Sierminska; Joachim R. Frick; Markus M. Grabka (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
Welfare-oriented analyses of economic outcome measures such as income and wealth generally rest on the assumption of pooled and equally shared resources among all household members. Yet the lack of individual-level data hampers the distribution of income and wealth within the ousehold context. Based on unique individual-level wealth data from the German Socio-Economic Panel (SOEP), this paper challenges the implicit assumption of internal redistribution by considering an alternative definition of the aggregation unit and by controlling its effect on distribution and inequality analysis. We find empirical evidence for a significant gender wealth gap of about 30,000 euros in Germany, which amounts to almost 50,000 euros for married partners. Decomposition analyses reveal that this gap is mostly driven by differences in characteristics between men and women, the most important factor being the individual's own income and labor market experience. However, this finding holds only for the upper part of the wealth distribution and can be shown only with non-parametric decomposition methods due to the mean orientation of the parametric Oaxaca-Blinder technique. Differences in the lower part of the wealth distribution appear to be driven mostly by the wealth function, i.e., the way in which women transform their characteristics into wealth.
Keywords: D13; D31; D69; I31; 330; Wealth gap; wealth inequality; gender; SOEP